The Franciscans and Yaylaq Khatun - Kovács, Szilvia (Acta Orientalia Vilnensia, 2017)
This study explores two issues. The first topic, as the title suggests, deals with the appearance of the Franciscan Order and its expansion at the expense of the Dominicans on the southern Russian steppe in the second half of the thirteenth century. The second question is tied to one of the successes of the Franciscans: the conversion to Christianity of one of the wives of Nogay, the khanmaker, the powerful lord of the western regions of the Golden Horde. I will reconstruct what can be ascertained about this khatun, based on Latin, Muslim and Byzantine sources.